Social ecosystem health: confronting the complexity and emergence of infectious diseases - Possas Cristina de Albuquerque (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
The emergence and re-emergence of infectious diseases and their rapid dissemination worldwide are challenging national health systems, particularly in developing countries affected by extreme poverty and environmental degradation. The expectations that new vaccines and drugs and global surveillance would help reverse these trends have been frustrated thus far by the complexity of the epidemiological transition, despite promising prospects for the near future in biomolecular research and genetic engineering. This impasse raises crucial issues concerning conceptual frameworks supporting priority-setting, risk anticipation, and the transfer of science and technology's results to society. This article discusses these issues and the limitations of social and economic sciences on the one hand and ecology on the other as the main theoretical references of the health sciences in confronting the complexity of these issues on their own. The tension between these historically dissociated paradigms is discussed and a transdisciplinary approach is proposed, that of social ecosystem health, incorporating these distinct perspectives into a comprehensive framework.